Revealing the novel autophagy-related genes for ligamentum flavum hypertrophy in patients and mice model - Li, Peng; Fei, Cheng-shuo; Chen, Yan-lin; Chen, Ze-sen; Lai, Zhong-ming; Tan, Rui-qian; Yu, Yong-peng; Xiang, Xin; Dong, Jia-le; Zhang, Jun-xiong; Wang, Liang; Zhang, Zhong-min (Frontiers in Immunology, 2022)
Background. Fibrosis is a core pathological factor of ligamentum flavum hypertrophy (LFH) resulting in degenerative lumbar spinal stenosis. Autophagy plays a vital role in multi-organ fibrosis. However, autophagy has not been reported to be involved in the pathogenesis of LFH. Methods. The LFH microarray data set GSE113212, derived from Gene Expression Omnibus, was analyzed to obtain differentially expressed genes (DEGs). Potential autophagy-related genes (ARGs) were obtained with the human autophagy regulator database. Functional analyses including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, Gene Set Enrichment Analysis (GSEA), and Gene Set Variation Analysis (GSVA) were conducted to elucidate the underlying biological pathways of autophagy regulating LFH. Protein-protein interaction (PPI) network analyses was used to obtain hub ARGs. Using transmission electron microscopy, quantitative RT-PCR, Western blotting, and immunohistochemistry, we identified six hub ARGs in clinical specimens and bipedal standing (BS) mouse model. Results. A total of 70 potential differentially expressed ARGs were screened, including 50 up-regulated and 20 down-regulated genes. According to GO enrichment and KEGG analyses, differentially expressed ARGs were mainly enriched in autophagy-related enrichment terms and signaling pathways related to autophagy. GSEA and GSVA results revealed the potential mechanisms by demonstrating the signaling pathways and biological processes closely related to LFH. Based on PPI network analysis, 14 hub ARGs were identified. Using transmission electron microscopy, we observed the autophagy process in LF tissues for the first time. Quantitative RT-PCR, Western blotting, and immunohistochemistry results indicated that the mRNA and protein expression levels of FN1, TGFβ1, NGF, and HMOX1 significantly higher both in human and mouse with LFH, while the mRNA and protein expression levels of CAT and SIRT1 were significantly decreased. Conclusion. Based on bioinformatics analysis and further experimental validation in clinical specimens and the BS mouse model, six potential ARGs including FN1, TGFβ1, NGF, HMOX1, CAT, and SIRT1 were found to participate in the fibrosis process of LFH through autophagy and play an essential role in its molecular mechanism. These potential genes may serve as specific therapeutic molecular targets in the treatment of LFH.